Properties of nonstationary boundary operators in a full scale of Sobolev-type spaces - Chudinovich, I. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Properties of boundary-value operators are established for the system of equations of the theory of elasticity in the complete scale of spaces of Sobolev type.